(untitled) (Indian Journal of Chemistry (IJC), 2023)
A new method portraying the utility of lead tetraacetate as an oxidizing agent in the synthesis of α-sulfonyloxyketones from aryl ketones and sulfonic acids has been described. This methodology offers a new alternative for the synthesis of a series of α-sulfonyloxyketones with broad substrate scope, easy availability of reactants as well as the use of simple oxidant.